(3caGjI GdefJgi aj TQM HOGjI GdeHJOis - (3GdnerQpZjfGfj GdaQZGfj, CHh GdMSf, HQgGf GdOjf, Ydj Hf CHj HcQ Hf YHO GdLdjd, (B593 (3g`s ((3eOjfI TjQhRs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CYdi eYGde GdYde hCYdGeg hbO LQi Ydqj GdhYO aj eHOC HOGjI GdeHJOj Cf CTQMgG HJhajb Gddg JYGdi TQMG CQSeg HcaGjI GdefJgj aTQYJ ajg hGdhYO jShZ HYV GdeSGZ hMjf CcGO CJcF Yfg GJcGA GdaQGZ JHjfJs
(3BNQgG (B:s
(3hdfG Gf GdZdHI JfRd efRdI GdVQhQI aj EaGOI GdEHGMI CdG jQi Cfg CShGb GdeSdejf dG JNdh Yf GdeMQe hGdeSQhb hGdeZUhH heY Pdc jHGM GdJfGhd GYJeGOG Ydi GdZGdH hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B4\266s
(3cTa GdXfhf (B2\1501s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfajs